Public procurement as an innovation policy: Where do we stand? - Olga Chiappinelli; Leonardo M. Giuffrida; Giancarlo Spagnolo (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Economics and innovation scholars have long recognized the potential of public procurement to trigger innovation. To what extent has this potential been realized so far? What can be done to improve the performance of PPI in this regard? This paper addresses these issues by providing a literature survey of research on public procurement of innovation (PPI). After categorizing PPI instruments, the paper discusses existing interdisciplinary knowledge to answer four broad questions: i) Does PPI spur innovation? ii) How should PPI be designed to best spur innovation? iii) What are the main barriers to implement PPI? iv) What is the role of PPI in the innovation policy mix? The paper concludes with a discussion of future research needs and policy insights in light of current global challenges.
Keywords: H23; H57; O30; O31; O32; O35; O36; O38; 330; innovation; public procurement; public policy; R&D; green purchases